Praktikalitas Pengembangan Buku Siswa dengan Model Problem Based Learning Ber-integrasi Kemampuan Berfikir Kreatif untuk Meningkatkan Kreativitas Peserta Didik SMA - Yulisman, Bilhakil Putra; Usmeldi, Usmeldi (Jurnal Penelitian Pembelajaran Fisika, 2021)
The research was conducted based on field observations. The research conducted was educational research so that the observations were carried out in schools, namely high schools in the city of Padang. Observation activities refer to the learning system, implementation of learning and the practicality of educators in teaching and using teaching resources or textbooks. Observations were carried out by distributing questionnaires, interviews and field observations directly to educators and to students. The results obtained during the observation were that the students' books used had not been integrated with creative thinking skills. In addition, the available student books had not used the model in the 2013 curriculum that should have been applied in schools. This has an impact on the satisfaction of students in receiving learning. The results of the distributed questionnaires found that all aspects asked related to the learning system were below 80%. This is categorized as low for the SMA Negeri level in the city of Padang. Therefore, the development of student books by using models in the 2013 curriculum, one of which is the Problem based learning model to improve students' creative thinking skills, is deemed necessary. The formulation proposed in this study is how to develop a student book with a Problem Based Learning model that integrates practical high school students' creative thinking skills. The purpose of this study was to develop a student book with a problem based learning model that integrates creative thinking skills to improve the creative thinking skills of high school students. The research carried out includes R&D research with the development model used is the 4D model. The investigation carried out was the level of practicality of student books which were developed using a practicality questionnaire of educators and students which contained the benefits of use, time efficiency, ease of use and attractiveness. The research was carried out at SMAN 16 Padang. The research process was carried out well. Practical analysis of students and educators is carried out by analyzing the completed questionnaire and looking for the percentage of the implementation of the questionnaire given.The results obtained after the research from the analysis of students' book practicality questionnaires from the results obtained from the students' practicality sheets got very practical results and the teacher's practicality got very practical results. Aspects of ease of use and time efficiency get results in the practical category, while aspects of benefit and attractiveness get very practical results from educators and practical from students so it is stated that the student books developed are practical.